Development of Psychological Training Curriculum on Life Management for Adolescent’s Study - Hunsaen, Sunsuen; Potjanaareewong, Jiraporn (Ratchaphruek Journal, 2020)
The objectives of this research were: 1) to develop the psychology training curriculum on life management in study of adolescent, 2) determine its quality, and 3) evaluate its feasibility. The subjects in this research were 30 adolescent by purposive sampling. The instruments include: 1) The psychology training curriculum on life management in study of adolescent, 2) Content validity evaluation, 3) Life management in study of adolescent students test, 4) The Assessment for satisfaction of the psychology training curriculum on life management in study of adolescent. Data were analyzed using Index of Item– Objective Congruence, descriptive statistics and paired t-test. The results were as follows The Psychology Training Curriculum on Life Management in Study of Adolescent Contains topics Orientation, Selection, Optimization, Compensation and Post training. Quality inspection of psychology training curriculum by finding the content validity was at a consistency index between 0.80-1.00 and the results of learning life management in Study of Adolescent before and after admission to psychology training, differences at the level of statistical a significant .05 The trainees were satisfied with the Psychology Training Curriculum on Life Management in Study of Adolescent in the high level to the highest level.